CLINICAL ASPECTS OF IMMEDIATE DENTIN SEALING ASSOCIATED WITH INDIRECT TECHNIQUE - Roxana-Ionela Vasluianu; Sylvain Bonnel; Bruno Flores; Elena-Raluca Baciu; Dragoș Ilisei; Alice Murariu; Catalina Holban-Cioloca; Nicoleta Ioanid (Romanian Society of Oral Rehabilitation, 2021)
Providing a long-term survival both for dental tissue and bonding restoration is one of the current therapeutic objectives. Objective. To use a combined technique of immediate dentin sealing (IDS) to a freshly cut dentin and indirect bonding restoration. Material and methods. Vital lateral teeth with extensive coronary destruction, with incorrectly adapted amalgam/composite fillings and deficient occlusal morphology were treated by applying IDS and all-ceramic onlay. Discussion. The clinical-technological algorithm used in our clinical cases is well-known and included tooth preparations, impression making, provisionalization, laboratory fabrication and adhesive cementation. In all cases, the vitality of the teeth was preserved and there were no signs of hypersensitivity in the near future after the final fixing of the all-ceramic onlay. Conclusions. The association of the IDS technique with indirect bonding onlay in the treatment of extensive coronary lesions of the molars allows preservation of their vitality, ensures their increased resistance over time, preservation of a stable occlusion and even periodontal protection by precise rendering of the crown morphology, occlusal and interproximal contacts.